Thyroid cancer bios signaling (Research, Society and Development, 2022)
Thyroid cancer integrates subtypes that are involved in signaling pathways that result in biological activities, such as differentiation, proliferation, in the absence of disease, and cell survival. BRAF is a gene that encodes the protein kinase\threonine that integrates the MAPK\ERK signaling pathway, as RAF signals are activated by the MAPK\ERK kinase and activates ERK\receptors. The current integrative review addresses the concepts of biosignaling mechanisms involved in thyroid cancer. The methodology used was based on reviewing the contextual principles of signaling that occurs in types of thyroid cancer, such as epidemiological, etiological and physiological factors. This integrative literature review aims to update and show the importance of understanding the biosignaling of thyroid cancer, which aims to highlight the role of genes involved in each type of malignant thyroid neoplasm. studies provide the engagement creation of genetic mutation profile panels, which evidence scientific factors that help in understanding the etiological complexity of thyroid cancer.